Detection of human papillomavirus types in balanitis xerotica obliterans and other penile conditions. Issue 4 (August 1995) - Lau, P W; Cook, N; Andrews, H; Bracka, A; Myint, S H
Abstract : OBJECTIVES–To determine the prevalence of human papillomavirus (HPV) types 6, 11, 16 and 18 in foreskin biopsies from patients with balanitis xerotica obliterans (BXO) and other penile conditions. MATERIALS AND METHODS–Foreskin biopsy specimens from 24 patients with penile lesions and 5 control patients were analysed by type-specific polymerase chain reaction (PCR). RESULTS–HPV6 or HPV16 were not detected in patients with BXO. HPV6 was detected in 2 controls. CONCLUSIONS–Genital papillomaviruses do not have a strong association with BXO.